Siyasah Pandemi ‘Umar bin al-Khaṭṭāb (Politik Kesehatan ‘Umar bin al-Khaṭṭāb dalam Menghadapi Wabah ‘Amwās Tahun 17-18 H/638-639 M) - Masykur Rozi (Jurnal Hukum Islam, 2020)
This paper to analyze of the respons of Umar bin Khattab in facing the 'Amwas pandemic in 638-639 AD in the perspective of health politics; and find patterns of political health theory practiced by Umar bin Khattab when facing a health emergency. The political theory of health from Bjørkdahl & Carlsen used to construct historical data documented in the hadith and historical books into a theory. The research method used documentation and content analysis techniques. The results showed that, Umar bin Khattab placed health as an important element under the prospect of people's welfare. Umar bin Khattab understood the plague as a natural human reality. This belief used as a knowledge base in shaping policies for handling outbreaks. The first technical implementation is the transfer of limited autonomy to the amir to prevent conflicts of authority. The second implementation is the transfer of value which becomes the standard for practical policy formation. The communication tactics used by Umar bin Khattab were parables and idioms that were in accordance with the understanding capacity of the interlocutor to involve all parties to participate in handling the epidemic.